Dynamic cerebral autoregulation is unrelated to decrease in external carotid artery blood flow during acute hypotension in healthy young men. Issue 8 (21st June 2016) - Ogoh, Shigehiko; Sørensen, Henrik; Hirasawa, Ai; Sasaki, Hiroyuki; Washio, Takuro; Hashimoto, Takeshi; Bailey, Damian M.; Secher, Niels H.
Abstract : New Findings: What is the central question of this study? Dynamic cerebral autoregulation (CA) is impaired by sympathetic blockade, and the external carotid artery (ECA) vascular bed may prevent adequate internal carotid artery blood flow. We examined whether α1 ‐receptor blockade‐induced attenuation of dynamic CA is related to reduced ECA vasoconstriction. What is the main finding and its importance? α1 ‐Receptor blockade attenuated dynamic CA, but in contrast to our hypothesis did not affect the ECA blood flow response to acute hypotension. These findings suggest that the recovery of cerebral blood flow during acute hypotension is unrelated to vasoconstriction within the ECA territory. External carotid artery (ECA) vasoconstriction may defend internal carotid artery (ICA) blood flow during acute hypotension. We hypothesized that the α1 ‐receptor blockade‐induced delay in ICA recovery to the baseline level from acute hypoperfusion is related to attenuated ECA vasoconstriction. The ICA and ECA blood flow were determined by duplex ultrasound during thigh‐cuff release‐induced acute hypotension while the α1 ‐receptor blocker prazosin [1 mg (20 kg) −1 ] was administered to nine seated young healthy men. Both ICA (mean ± SD; by 17 ± 8%, P  = 0.005) and ECA (by 37 ± 15%, P  < 0.001) blood flow decreased immediately after occluded thigh‐cuff release, with a more rapid ICA blood flow recovery to the baseline level (9 ± 5 s) than for the ECA blood flow (17 ± 5 s; P  = 0.019). The ICA blood flow recovery from hypoperfusion was delayed with prazosin (17 ± 4 s versus control 9 ± 5 s, P  = 0.006), whereas ECA recovery remained unchanged ( P  = 0.313) despite a similar reduction in mean arterial pressure (−20 ± 4 mmHg versus control −23 ± 7 mmHg, P  = 0.148). These findings suggest that α1 ‐receptor blockade‐induced attenuation of the ICA blood flow response to acute hypotension is unrelated to the reduction in ECA blood flow. The sympathetic nervous system via the ECA vascular bed does not contribute to dynamic CA during acute hypotension. Abstract :